Promotional tone in reviews of menopausal hormone therapy after the Women's Health Initiative: an analysis of published articles. - Adriane Fugh-Berman; Christina Pike McDonald; Alicia M Bell; Emily Catherine Bethards; Anthony R Scialli (PLoS Medicine)
Background Even after the Women's Health Initiative (WHI) found that the risks of menopausal hormone therapy (hormone therapy) outweighed benefit for asymptomatic women, about half of gynecologists in the United States continued to believe that hormones benefited women's health. The pharmaceutical industry has supported publication of articles in medical journals for marketing purposes. It is unknown whether author relationships with industry affect promotional tone in articles on hormone therapy. The goal of this study was to determine whether promotional tone could be identified in narrative review articles regarding menopausal hormone therapy and whether articles identified as promotional were more likely to have been authored by those with conflicts of interest with manufacturers of menopausal hormone therapy. Methods and findings We analyzed tone in opinion pieces on hormone therapy published in the four years after the estrogen-progestin arm of the WHI was stopped. First, we identified the ten authors with four or more MEDLINE-indexed reviews, editorials, comments, or letters on hormone replacement therapy or menopausal hormone therapy published between July 2002 and June 2006. Next, we conducted an additional search using the names of these authors to identify other relevant articles. Finally, after author names and affiliations were removed, 50 articles were evaluated by three readers for scientific accuracy and for tone. Scientific accuracy was assessed based on whether or not the findings of the WHI were accurately reported using two criteria: (1) Acknowledgment or lack of denial of the risk of breast cancer diagnosis associated with hormone therapy, and (2) acknowledgment that hormone therapy did not benefit cardiovascular disease endpoints. Determination of promotional tone was based on the assessment by each reader of whether the article appeared to promote hormone therapy. Analysis of inter-rater consistency found moderate agreement for scientific accuracy (κ=0.57) and substantial agreement for promotional tone (κ=0.65). After discussion, readers found 86% of the articles to be scientifically accurate and 64% to be promotional in tone. Themes that were common in articles considered promotional included attacks on the methodology of the WHI, arguments that clinical trial results should not guide treatment for individuals, and arguments that observational studies are as good as or better than randomized clinical trials for guiding clinical decisions. The promotional articles we identified also implied that the risks associated with hormone therapy have been exaggerated and that the benefits of hormone therapy have been or will be proven. Of the ten authors studied, eight were found to have declared payment for speaking or consulting on behalf of menopausal hormone manufacturers or for research support (seven of these eight were speakers or consultants). Thirty of 32 articles (90%) evaluated as promoting hormone therapy were authored by those with potential financial conflicts of interest, compared to 11 of 18 articles (61%) by those without such conflicts (p=0.0025). Articles promoting the use of menopausal hormone therapy were 2.41 times (95% confidence interval 1.49-4.93) as likely to have been authored by authors with conflicts of interest as by authors without conflicts of interest. In articles from three authors with conflicts of interest some of the same text was repeated word-for-word in different articles. Conclusion There may be a connection between receiving industry funding for speaking, consulting, or research and the publication of promotional opinion pieces on menopausal hormone therapy.